Psychometric Analysis of the Perceived Stress Scales (PSS-14 and PSS-10) in a group of Teachers from Copiapó, Chile - Jorquera-Gutiérrez, Ricardo (2023)
Background: Perceived stress refers to the degree to which people perceive the demands of their environment as unpredictable and uncontrollable. The PSS-14 and PSS- 10 scales are the most widely used instruments worldwide to assess this construct. Objective: To describe the psychometric properties of the EEP 14 and 10 items in Chilean teachers, and to investigate the structural invariance of its models according to teachers’ gender Method: An instrumental study was carried out in a sample of 206 teachers. Results: Confirmatory factor analysis, using a robust maximum likelihood (MLR) method, showed the best fit indicators in the models of two related factors: in the PSS-14 (X2 = 166.693, df = 76, p < .001; CFI = .918; TLI = .901; RMSEA = .076) and in the PSS-10 (X2 = 59.979, df = 34, p < .001; CFI = .968; TLI = .957; RMSEA = .061). The McDonald’s ω coefficients were favorable for the factors of both scales. Likewise, the invariance of the two- factor structure for men and women in the two instruments was verified. Conclusion: It is concluded that these antecedents would support the use of these instruments in Chilean teachers Authorship contributionRJG and FGD: all authors participated in drafting and revising the manuscript.